The Relationship Between Childhood Neglect and Malevolent Creativity: The Mediating Effect of the Dark Triad Personality - Jia, Xuji; Wang, Qingjin; Lin, Lin (Frontiers in Psychology, 2020)
In addition to what we know as benevolent creativity, which involves originality and usefulness, creativity also includes malevolent creativity, which involves the application of creative ideas to intentionally harm others. This study aimed to explore the environmental and individual predictors of malevolent creativity. We investigated the relationship among childhood neglect, Dark Triad personality traits and malevolent creativity and examined the mediating role of Dark Triad personality. A large sample (N=991) of Chinese undergraduate students completed the childhood neglect scale, the 12-item Dirty Dozen and the Malevolent Creativity Behavior Scale. Structural equation modeling demonstrated that childhood neglect was positively related to individual malevolent creativity, and the Dark Triad partially mediated this relationship. Additionally, gender differences were found, such that childhood neglect had a stronger effect on malevolent creativity through the Dark Triad among males than females. The results were discussed from the perspectives of life history theory and social information processing theory.